The effect of technology, social media and knowledge shared between gen x'ers and gen y towards effective communication at Tanah Makmur Berhad / Siti Shahirah Mohamad Noor - Mohamad Noor, Siti Shahirah (Faculty of Business Management, 2017)
This study was to investigate the relationships of technology, social media and knowledge towards the effective communication at different generation. The concem of this study is to discover whether the technology, social media and knowledge shared have influence in the communication based on difference generation. The first objective of the study is to investigate the relationship between all the elements of communication toward the effective communication. The researcher was used correlational test to identify the relationship. Secondly. is to identify the most major elements of communication that contributed towards effective communication. The researcher was used regression test to discover the most major element by look at significant or not. Thirdly. to investigate either Gen X'er or Gen Y that is most effective in communication according to the elements of communication. The researcher was used independent t-test to compare the mean between the two generation.